Analisis Mutu Pelayanan Prolanis dan Kepuasan Peserta Klub Menggunakan Metode Importance Performance Analysis - Yasrin, Palji Alpala; Yunita, Jasrida; Susanti, Nurvi (Jurnal Kesehatan Komunitas, 2023)
Every year, the working area of Gunung Toar Community Health Center views an increase in the number of patients suffering from diabetes mellitus and hypertension. However not everyone with hypertension and diabetes mellitus received prolanis, and neither the Gunung Toar Community Health Center nor BPJS Health have evaluated the quality of prolanis services. The research's objective was to use the Importance Performance Analysis (IPA) method to assess participant satisfaction and the quality of services provided by the chronic disease management program.  It is a mixed-methods research design. The study was carried out in May and June of 2022 in the working area of the Gunung Toar Community Health Center in Kuantan Singingi Regency. There were 533 individuals in the population. Importance Performance Analysis was used for both quantitative analysis, with a sample of 100 respondents, and qualitative analysis, with five informants conducted through in-depth interviews. Based on the study's findings, it was discovered that participant satisfaction was 96.51% overall, officer reliability was 92.68%, responsiveness was 97.45%, physical evidence was 99.50%, assurance was 98.18%, and empathy was 96.02%. More personnel in charge of prolanis in each club, a stronger prolanis team, increased cross-sectoral support, better management of accountability document archiving, and regular, quarterly, and annual evaluations of prolanis operations are still required.